Agama Sebagai Proyek Kemanusiaan: Telaah Filsafat Agama atas Pemikiran Gus Dur Tentang Pluralisme dan Kemanusiaan di Indonesia: indonesia - Faishal, Muhammad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
In Abdurrahman Wahid’s (Gus Dur) perspective, religion is not only a spiritual path to God but also a means to realize humanitarian values in communal life. In the context of Indonesia's plural society, Gus Dur positioned religion as a tool to preserve diversity and protect the rights of minority groups. This study aims to examine Gus Dur's thought through the lens of the philosophy of religion, focusing on the concepts of pluralism and humanity. Using a qualitative descriptive method and a philosophical-hermeneutical analysis, the research explores various primary and secondary texts, including speeches, writings, and policies reflecting Gus Dur’s commitment to pluralism. The findings reveal that Gus Dur viewed faith as a social responsibility, not merely a private relationship with God. He advocated interreligious dialogue, respect for differences, and solidarity with marginalized groups as integral to a sincere expression of religious belief. The study concludes that religion can serve as a humanitarian project when practiced openly, emphasizing justice, compassion, and solidarity. This research contributes to the development of a contextual philosophy of religion and opens new avenues for discourse on the role of religion in upholding humanity within pluralistic societies.